Volume 1: Advanced Packaging; Emerging Technologies; Modeling and Simulation; Multi-Physics Based Reliability; MEMS and NEMS; M 2013
DOI: 10.1115/ipack2013-73171
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electrode Material on Joint Strength of Soldered Joints With Sn-Bi and Sn-Bi-Sb Lead-Free Solder Balls

Abstract: The aim of this study is to investigate the joint properties of Sn-58mass%Bi and Sn-57mass%Bi-0.5mass%Sb low-melting lead-free solder balls on the electroless Ni/Au and Ni/Pd/Au plated Cu electrodes fabricated with a lead-free plating solution. Compared with the conventional Ni plating solution containing lead, the soldered joints with Ni/Au and Ni/Pd/Au electrodes fabricated with the lead-free plating solution showed comparable joint properties. In the joints with Ni/Pd/Au electrodes, ball shear force increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Finally, dog-bone-type specimens (Figure 1) were machined from the cylindrical Sn-40Bi-based alloy ingots for the tensile tests. enhance the mechanical properties and wettability of Pb-free solders for green electronic devices [16][17][18][19][20][21][22]. Takao et al [23], for instance, reported that Sn-Bi and Sn-Bi-Cu alloys exhibit superplasticity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, dog-bone-type specimens (Figure 1) were machined from the cylindrical Sn-40Bi-based alloy ingots for the tensile tests. enhance the mechanical properties and wettability of Pb-free solders for green electronic devices [16][17][18][19][20][21][22]. Takao et al [23], for instance, reported that Sn-Bi and Sn-Bi-Cu alloys exhibit superplasticity.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, several research groups have focused on manufacturing new alloys doped with micro-/nanometer-sized particles, e.g., Ni, Fe, Zn, Ag, Al, ZrO 2 , Al 2 O 3 , TiO 2 , etc., to enhance the mechanical properties and wettability of Pb-free solders for green electronic devices [16][17][18][19][20][21][22]. Takao et al [23], for instance, reported that Sn-Bi and Sn-Bi-Cu alloys exhibit superplasticity.…”
Section: Introductionmentioning
confidence: 99%